Strengthening Post-Crisis Fiscal Credibility Fiscal Councils on the Rise - A New Dataset - Debrun, Xavier (International Monetary Fund, 2014)
Institutions aimed at constraining policy discretion to promote sound fiscal policies are once again at the forefront of the policy debate. Interest in "fiscal councils," independent watchdogs active in the public debate, has grown rapidly in recent years. This paper presents the first cross-country dataset summarizing key characteristics of fiscal councils among IMF members. The data documents a surge in the number of fiscal councils since the crisis. It also illustrates that well-designed fiscal councils are associated with stronger fiscal performance and better macroeconomic and budgetary forecasts. Key features of effective fiscal councils include operational independence from politics, the provision or public assessment of budgetary forecasts, a strong presence in the public debate, and the monitoring of compliance with fiscal policy rules